Nucleoside adducts are formed by cooperative reaction of acetaldehyde and alcohols: possible mechanism for the role of ethanol in carcinogenesis. - Fraenkel-Conrat, H (1988)
The exocyclic amino groups of ribonucleosides and deoxyribonucleosides react rapidly at ambient temperature with acetaldehyde and alcohols to yield mixed acetals [--NH--CH(CH3)OR]. Nucleotides and nucleoside di- and triphosphates also react. Depending on the nucleoside used and on the relative amounts of aldehyde, alcohol, and water, preparative reactions reach equilibrium with yields up to 75% in a few hours. The structures have been confirmed by fast atom bombardment MS and proton NMR. Half-lives at 37 degrees C have been determined, and maximum stability is in the pH range of 7.5-9.5. In the absence of alcohol, acetaldehyde-nucleoside adducts could be isolated at 4 degrees C, but these were too unstable to characterize except for their UV spectra, also at 4 degrees C. Ethanol is often present in human blood and tissues, and acetaldehyde is its initial metabolic product, as well as being formed by many other metabolic processes. Both chemicals have separately been implicated in carcinogenic and other cytopathologic processes, but no cooperative mechanism has been proposed. The reactions reported here are of biological concern because they also occur in dilute aqueous solution. These findings supply a mechanism by which ethanol can be covalently bound to nucleic acids under physiological conditions.